Efficacy and Safety of Ascending Dosages of Moxidectin and Moxidectin-albendazole Against Trichuris trichiura in Adolescents: A Randomized Controlled Trial. (2nd May 2019) - Keller, Ladina; Palmeirim, Marta S; Ame, Shaali M; Ali, Said M; Puchkov, Maxim; Huwyler, Jörg; Hattendorf, Jan; Keiser, Jennifer
Abstract: Background: Preventive chemotherapy is the main strategy to control soil-transmitted helminth (STH) infections. Albendazole and mebendazole are ubiquitously used, but they are not sufficiently effective against Trichuris trichiura . Moxidectin might be a useful addition to the small drug armamentarium. However, the optimal dosage of moxidectin alone and in combination with albendazole against T. trichiura and other STHs has not yet been determined. Methods: A Phase II, randomized, placebo-controlled, dose-finding trial was conducted in 2 secondary schools on Pemba Island, Tanzania. Using a computer-generated list, T . trichiura– infected adolescents were randomly assigned to 7 treatment arms: 8, 16, or 24 mg of moxidectin monotherapy; 8, 16, or 24 mg of moxidectin plus 400 mg of albendazole combination therapy; or placebo. The primary outcome was cure rate (CR) against T. trichiura, analyzed 13 to 20 days after treatment by quadruple Kato-Katz thick smears. Results: A total of 290 adolescents were enrolled (41 or 42 per arm). CRs against T. trichiura were 43, 46, and 44% for 8, 16, and 24 mg of moxidectin alone, respectively; 60, 62, and 66% for the same moxidectin dosages plus 400 mg of albendazole, respectively; and 12% for placebo. The moxidectin-albendazole arms also revealed higher CRs and egg reduction rates against hookworm than the monotherapy arms. Moxidectin and its combination with albendazole were well tolerated. Conclusions: Moxidectin-albendazole is superior to moxidectin. There is no benefit of using doses above 8 mg, which is the recommended dose for onchocerciasis. The moxidectin-albendazole combination of 8 mg plus 400 mg should be investigated further to develop recommendations for appropriate control of STH infections. Clinical Trials Registration: NCT03501251. Abstract : Our randomized dose-finding trial of 290 adolescents in Tanzania found that a moxidectin-albendazole combination is superior to moxidectin alone for curing Trichuris trichiura and hookworm infections. A flat, dose-response relationship was observed for both treatments.